Hypodontia and Hyperdontia as Examples of Developmental Disorders in Tooth Number: Literature Review and Clinical Case Reports - Martyna Wojda; Aleksandra Wielgosz (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: Hypodontia and hyperdontia are two common developmental dental anomalies characterized by an abnormal number of teeth and they present a significant challenge in dentistry, affecting both the functionality and aesthetics of the dentition. Hypodontia refers to the congenital absence of one or more teeth, while hyperdontia is characterized by the presence of supernumerary teeth in the oral cavity. These conditions can lead to various complications, such as bite issues, speech disorders, and difficulties in daily functioning.   State of knowledge: Tooth number anomalies can have various causes, ranging from evolutionary reduction in dentition due to lifestyle changes over the years. The reduction in the number of teeth is currently among the most common developmental dental defects. Environmental factors also influence tooth number, acting as either local or general factors. Genetic influences should also be considered, as hypodontia and hyperdontia can be hereditary, and gender also plays a role in the predisposition to these conditions. Numerical anomalies in teeth can also be a symptom of certain genetically determined syndromes. Summary: Hypodontia and hyperdontia are examples of developmental disorders related to the number of teeth in the oral cavity, with various underlying causes. Diagnosis and subsequent treatment are crucial in managing these conditions. These disorders may require long-term therapies involving different areas of dentistry and interdisciplinary cooperation or may simply require ongoing clinical and radiological observation. Treatment depends on the severity of the disorder and the individual needs of the patient. However, thanks to advances in diagnosis and treatment, it is possible to effectively prevent complications.